Febrile neutropenia in cancer patients; microbiology and clinical outcome of empirical antimicrobial therapy - Mustafa, Waqar Mian (Prince of Songkla University, 2014)
Thesis (M.Pharm., Clinical Pharmacy)--Prince of Songkla University, 2013